The Effect of Work Environment on Employees' Job Satisfaction: Empirical Evidence from the Banking Industry - Meku Lelo, John (Universitas Airlangga, 2024)
Objective: Despite streams of literature that establish the interdependence between the work environment and employees' job satisfaction (EJS), a debate on the topic has not been concluded. The current study employed Herzberg's two-factor theory to investigate the effect of the work environment on EJS in the context of the baking industry. Design/Methods/Approach: A cross-sectional questionnaire survey and simple random sampling were utilized to collect data from 417 employees across commercial banks. Subsequently, confirmatory factor analysis (CFA) and structural equation modeling (SEM) were employed for data analysis. Findings: The results indicate a positive relationship between the work environment and EJS. Specifically, the physical work environment, remuneration, social work environment, job security, and safety demonstrated positive and significant effects on EJS. Originality/Value: The novelty of this study lies in its specific focus on the banking industry, the comprehensive inclusion of various dimensions of the work environment, and the utilization of the two-factor theory. It surpasses the narrow focus of previous research, which concentrated on a single aspect of the work environment. With this approach, the study offers in-depth insights to banking industry stakeholders on how work environments directly impact EJS. Practical/Policy implication: To foster conducive work environments in the banking industry, managers should prioritize designing comfortable workplace environments by providing ergonomic furniture, competitive remuneration, a visually appealing atmosphere, robust safety measures and job security, and a supportive and harmonious social work environment, which, according to the study findings, are the drivers of EJS.